Conserved organ-specific microbial assemblages in different populations of a terrestrial crab - Bacci, Giovanni; Fratini, Sara; Meriggi, Niccolò; Cheng, Christine L. Y.; Ng, Ka Hei; Pindo, Massimo; Iannucci, Alessio; Mengoni, Alessio; Cavalieri, Duccio; Cannicci, Stefano (Frontiers in Microbiology, 2023)
Microorganisms are ubiquitous in the environment and provide genetic and physiological functions to multicellular organisms. Knowledge on the associated microbiota is becoming highly relevant to understand the host’s ecology and biology. Among invertebrates, many examples of endosymbiosis have been described, such as those in corals, ants, and termites. At present, however, little is known on the presence, diversity, and putative roles of the microbiota associated to brachyuran crabs in relation to their environment. In this work we investigated the associated microbiota of three populations of the terrestrial brachyuran crab Chiromantes haematocheir to find evidence of a conserved organ-specific microbiome unrelated to the population of origin and dissimilar from environmental microbial assemblages. Bacterial 16S rRNA gene and fungal ITS sequences were obtained from selected crab organs and environmental matrices to profile microbial communities. Despite the presence of truly marine larval stages and the absence of a gregarious behaviour, favouring microbiota exchanges, we found common, organ-specific microbiota, associated with the gut and the gills of crabs from the different populations (with more than 15% of the genera detected specifically enriched only in one organ). These findings suggest the presence of possible functional roles of the organ-specific microbiota.